KEPUASAN KERJA SEBAGAI MEDIASI HUBUNGAN KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN 78 (Studi pada Puri Saron Hotel Group di Bali) - Anak Agung Ketut Sri Asih; I Wayan Arta Artana (Forum Manajemen, 2014)
This study aimed to determine the effect of direct and indirect communication,organizational culture, and job satisfaction on employee performance in Pui SaronBali Hotel Group. The results obtained from this study are: (1) there is positivecommunication, organizational culture, and job satisfaction is directly on theperformance of employees at Puri Saron Hotel Group Bali, (2) there is a positiveindirect effect between organizational culture on employee performance throughmediation of job satisfaction, (3) job satisfaction is not a variable mediating theindirect relations communications and employee performance at Puri Saron HotelGroup Bali. The greatest indicator of the role of each variable are: (1) action oncommunication, (2) integration of the organizational culture, (3) satisfaction withpromotion on job satisfaction, and (4) ability to cooperate in the performance ofemployee.